2015
DOI: 10.3389/fpsyg.2015.00207
|View full text |Cite
|
Sign up to set email alerts
|

“Wesley says”: a children’s response inhibition playground training game yields preliminary evidence of transfer effects

Abstract: Recent studies suggest that the response inhibition ability of children can be modified through training. Based on the notion of embodied cognition, we investigated transfer effects of a 7-day training program using a game named “Wesley says” in 8- to 12-year-old children (n = 15). The game consists of providing commands for performing simple body actions, the actual execution of which is conditional upon the preceding verbal expression “Wesley says.” Training effects were assessed with a computer-based visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
2
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 42 publications
(51 reference statements)
3
17
2
13
Order By: Relevance
“…The dissociation between conflict resolution in the Simon and the Stroop tasks in Experiment 1 (and replicated in Experiment 2) has been consistently reported in previous studies (Liu, Park, Gu, & Fan, 2010;Pratte et al, 2010). Despite latent variable analyses indicating that the Stroop task (specifically Stroop-colour) and the anti-saccade task load on a single factor (Friedman & Miyake, 2004), other inhibition training studies have found no evidence of transfer to the Stroop task (Enge et al, 2014;Millner et al, 2012;Zhao, Chen, Fu, & Maes, 2015). For example, in Enge et al' (2014) large scale (N = 122) training study, in which participants trained on an adaptive go/no-go task and a stop-signal task intermittently over 3 weeks, significant improvements were observed in the trained task, but there was no transfer to the Stroop task.…”
Section: Discussionsupporting
confidence: 72%
“…The dissociation between conflict resolution in the Simon and the Stroop tasks in Experiment 1 (and replicated in Experiment 2) has been consistently reported in previous studies (Liu, Park, Gu, & Fan, 2010;Pratte et al, 2010). Despite latent variable analyses indicating that the Stroop task (specifically Stroop-colour) and the anti-saccade task load on a single factor (Friedman & Miyake, 2004), other inhibition training studies have found no evidence of transfer to the Stroop task (Enge et al, 2014;Millner et al, 2012;Zhao, Chen, Fu, & Maes, 2015). For example, in Enge et al' (2014) large scale (N = 122) training study, in which participants trained on an adaptive go/no-go task and a stop-signal task intermittently over 3 weeks, significant improvements were observed in the trained task, but there was no transfer to the Stroop task.…”
Section: Discussionsupporting
confidence: 72%
“…Verbruggen, Adams, and Chambers () found that training of inhibitory control reduced monetary risk‐taking in a subsequent gambling task. Finally, Zhao, Chen, Fu, and Maes () used a response inhibition playground training game in a real‐world setting in children and observed improved performance on a non‐trained computer‐based response inhibition task. However, Thorell, Lindqvist, Bergman Nutley, Bohlin, and Klingberg () and Enge et al.…”
Section: Introductionmentioning
confidence: 99%
“…Aquí se debe denominar lo más rápidamente posible (e intentando no cometer errores) el color de la tinta en la que está escrita la palabra. Cuando el color no coincide con la palabra escrita se genera un fuerte fenómeno de interferencia, el cual se entiende que se controla a través del proceso de inhibición (e.g., Friedman & Miyake, 2004;Zhao, Chen, Fu, & Maes, 2015). La tarea en su versión original implica láminas en las que se presentan las condiciones antes mencionadas, mientras que el administrador registra y puntúa las respuestas del participante.…”
Section: Tareas Informatizadasunclassified